Analisis Bahan Ajar IPS di Sekolah Dasar - Ganes Gunansyah, (Pendidikan Sekolah Dasar, 2009)
Capabilities inherent in the figure of one professional teacher relates to the ability to develop the field of science instructional materials that are occupied or in accordance with the curricular context and needs of learners (pedagogical content knowledge). In the Government Regulation (PP) Number 19 of 2005 provision 20, hinted that the teachers are expected to develop teaching materials, which then reinforced through the Regulation of the Minister of National Education (Permendiknas) Number 41 year 2007 about Standard Process, which among other things about the learning process that requires planning for educators on the educational unit to develop Learning Implementation Plan (RPP). Teachers are expected to further develop and implement instructional materials in learning. However, important issues often faced by teachers in the learning activity is to select or determine the teaching materials or instructional materials that are appropriate in order to help students achieve competence. Based on the structure of the SBC, IPS study materials include the ability to understand a set of facts, concepts, and generalizations about (1) social and cultural systems, (2) people, places and environments, (3) economic behavior and welfare, (4) time, continuity and changes, (5) national and state systems. This paper was based on the importance of conceptual analysis of teaching materials for teachers to avoid a mistake to identify the types of learning materials and be able to meet the elements kecakupan, adequacy and depth of learning materials so that the level of student mastery of competencies contained in the Competency Standards (SK) and Basic Competency ( KD) can be achieved